A avaliação como instrumento de melhoria da qualidade da alfabetização: uma análise da experiência do programa alfabetização na idade certa (PAIC) - Alves, Marly dos Santos (2010)
This research was, in general, see how the actions taken by the axis of evaluation of the Literacy in the Middle One (PAIC) have contributed to improving the quality of education in the early years of elementary school. Specifically intended to look as it did the process of the PAIC in public schools, to identify the level of knowledge that teachers had on the design of assessment promoted by PAIC; raise with which the teachers received training to work with the program; see how teachers use the teaching materials in the classroom, identifying the changes in the practice of literacy teachers provided by the disclosure of the evaluation results by student, seeking information about monitoring the Education Department in the activities developed in schools with the PAIC. Literacy is a stage of schooling in which children need to acquire the basic skills of reading and writing. According to the data with the results of the state of Ceara in the evaluations conducted by the Ministry of Education and Culture, students enrolled in the early years of elementary school had a critical and very critical reading and writing. Thus was created the Literacy Program at Age One, whose goal is to alphabetize all children by age 7, bringing the schools a new teaching methodology and assessment, by thus facilitate the task of teacher literacy and raise the quality education in the state. Accordingly, after 3 years of program implementation, carried out a qualitative research with a sample of ten teachers from a city whose students participate in PAIC since its implementation in the state and with significant changes in these three years . Were used as research tools: a semistructured interview and a bibliographic authors in the field of literacy assessment, the National Curriculum Guidelines, the Literacy Program at Age One and Continuing Training Program for Teachers of years / grades of elementary school. Data analysis revealed a significant change in the teacher evaluation practices and performance of the students that the evaluation by the program, demonstrating that the PAIC came to improve the quality of education in the early years of elementary school.